PENILAIAN KETERAMPILAN COMPUTATIONAL THINGKING SISWA DALAM PEMBELAJARAN IPA MELALUI AKTIVITAS UNPLUGGED BERDASARKAN REFLEKSI GURU SEKOLAH DASAR - Arunita Simanjuntak; Putri Anita; Job Psalmer Jason; Neni Hermita; Rifqa Gusmida Syahrun Barokah (STKIP Subang, 2026)
The development of computational thinking (CT) has become increasingly important in primary education, particularly in supporting students’ problem-solving skills in the 21st century. However, assessing CT skills, especially through process-based observation, remains a challenge. This study aims to describe students’ computational thinking skills in science learning through unplugged activities based on researcher reflection on teacher-reported observations. The study employed a descriptive quantitative approach involving 8 primary school teachers as respondents. Data were collected using a Likert-scale questionnaire designed based on three CT indicators: algorithmic thinking, pattern recognition, and debugging. The data were analyzed using descriptive statistics, including mean, median, and standard deviation. The results showed that all CT indicators were categorized as very high, with debugging having the highest mean score, followed by algorithmic thinking and pattern recognition. The relatively low standard deviation and interquartile range indicated consistent responses among teachers. These findings suggest that unplugged activities effectively support the development of students’ computational thinking skills by emphasizing active, reflective, and structured problem-solving processes. Therefore, integrating unplugged activities into science learning can be an effective strategy to foster CT skills at the primary school level.